LRP-1 Pathway Targeted Inhibition of Vascular Abnormalities in the Retina of Diabetic Mice. (3rd April 2017) - Hossain, Ahamed; Tauhid, Lamiya; Davenport, Ian; Huckaba, Thomas; Graves, Richard; Mandal, Tarun; Muniruzzaman, Syed; Ahmed, Syed A.; Bhattacharjee, Partha S.
ABSTRACT: Purpose : The cell surface LDL (low-density lipoprotein) receptor-related protein-1 (LRP-1) is important for lipid transport and several cell signaling processes. Human apolipoprotein E (apoE) is a ligand of LRP-1. We previously reported that a short peptide (apoEdp) mimicking the LRP-1 binding region of apoE prevents hyperglycemia-induced retinal endothelial cell dysfunction in vitro . The in-vivo outcome of apoE-based peptidomimetic inhibition of LRP-1 in the treatment of diabetic retinopathy is unknown. Methods : Six months after streptozotocin induction of diabetes, male C57Bl/6 mice were intravitreally inoculated with apoEdp in a controlled release formulation. On the 15th day post-apoEdp treatment, mouse retinas were harvested to examine (1) blood–retinal–barrier (BRB) permeability by Evans blue dye, inflammatory leukostasis by concanavalin staining of leukocytes and LRP-1 pathway-related protein expression by Western blot analysis and gelatin zymography. Results : Intravitreal apoEdp treatment of diabetic mice significantly reduced Evans blue extravasation and the number of adherent leukocytes in the diabetic mouse retinas. ApoEdp treatment inhibited the expression of extracellular matrix (ECM) degrading proteases heparanase and MMP-2, and restores the BRB tight junction proteins occludin and ZO-1. ApoEdp treatment also inhibited Wnt/β-catenin-related expression of pro-inflammatory molecules ICAM-1, HIF-1α, and VEGF through negative regulation by LRP-1. Conclusion : Intravitreal apoEdp treatment of diabetic mice resulted a significant decrease in retinal vascular abnormalities through downregulation of LRP-1-related ECM protein degradation and Wnt/β-catenin-related pro-angiogenic molecules.